Pete the cat saves christmas eaudiobook - Litwin, Eric (Pete the Cat., 2013)
A New York Times bestselling Pete the Cat holiday picture book! Spend the holidays with your favorite blue cat! In this rockin' spin on the traditional tale The Night Before Christmas, Pete the Cat proves that giving your all in the spirit of Christmas is the totally groovy thing to do. The fun never stops—don't miss Pete's other spin on a holiday classic, Pete the Cat's 12 Groovy Days of Christmas. Don't miss Pete's other adventures, including Pete the Cat: I Love My White Shoes, Pete the Cat: Rocking in My School Shoes, Pete the Cat and His Four Groovy Buttons, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the New Guy, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, and Pete the Cat and the Perfect Pizza Party.